Tuning the austenite and martensite phase fraction in ferromagnetic shape memory alloy ribbons of Ni45Co5Mn38Sn12 - Lakhani, Archana (2014)
The ferromagneticshape memoryalloy ribbons with composition Ni45Co5Mn38Sn12 are shown to have field induced kinetically arrested ferromagnetic austenite phase down to the low temperature due to hindered martensite transformation. This gives rise to the coexisting martensite and austenite phases in a wide range of temperature and field. Here, we show a systematic rise in arrested austenite phase with the reduction in martensite phase quantitatively by various magnetization measurements. The fraction of these coexisting phases can be tuned in “field-temperature” space. Further, we show that the “domain” of tunability varies with temperature.